Measurement of Autoantibodies Against Fibrinogen and Fibrin Degradation Products by Enzyme-Linked Immunoassay - Whitaker, A N; McFarlane, J R; Rowe, E A; Lee, K; Masci, P P (Thrombosis and Haemostasis, 1985)
We have devised a simple enzyme immunoassay to detect and quantitate autoantibodies against derivatives of fibrinogen. This assay has been applied with a range of antigens including a fibrinogen lysate (containing X, Y, D and E), D dimer, D dimerE and a preparation of high molecular weight complexes derived from crosslinked fibrin. We have found that autoantibodies interacting with these antigens can be detected in varying concentrations in most sera from both normal subjects and patients with a variety of diseases and are evidently of mixed Ig class. These autoantibodies are directed against at least several cryptic antigens which appear during fibrinogen/fibrin degradation and some appear to be directed specifically against cross- linked fibrin derivatives. No clear disease correlates have yet emerged but a relationship between elevated levels and prior infective, thrombotic, inflammatory or traumatic disorders is likely. It is suggested that these autoantibodies may contribute to the catabolism of fibrinogen derivatives, provide a marker of thrombosis, and sometimes produce pathologic effects.
Keywords: Fibrin(ogen) degradation products; Autoimmunity; Intravascular coagulation; Enzyme-linked immunoassay